STUDENTS PERCEPTIONS TOWARDS THE INDONESIAN LANGUAGE COURSE - Elva Riezky Maharany; Nuse Aliyah Rahmati; Basori Basori (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2022)
Directorate General of Higher Education Ministry of Education and Culture Republic of Indonesia issued a decree named SK Dirjen Number 43 regarding the implementation of the personality development course in higher education. The vision of teaching those courses, including teaching Indonesian language, is to provide source of values and guidelines in the development and implementation of study programs to lead students to establish their personality as Indonesian people. The study brings comprehensions about students acceptance of teaching the course and be useful for study programs that offers ELE. The programs can use the findings as a reference how they have to design their curriculum to meet students needs as well as in line with the government regulations. this study applied a phenomenology under the qualitative approach. Based on the result of the data analysis to capture students of English Language Education (ELE) perceive the teaching of Bahasa Indonesia course at the university level, the researchers put into two major themes. The first theme is students positive perceptions Bahasa Indonesia course, while the last is students negative perception towards similar course.